MENEMUKENALI FAKTOR PENYEBAB KESULITAN BELAJAR SISWA YANG MENGALAMI UNDERACHIEVER [IDENTIFYING FACTORS CAUSED LEARNING DIFFICULTIES FOR STUDENTS WHO HAVE UNDERACHIEVER] - Yusuf, Nur Mawakhira; Kasmi, K (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2022)
Underachiever is not impossible to be experienced by the people closest to us where people who have a high IQ are very susceptible to disappointment based on the expectations given to them based on individual knowledge of their intelligence scores. Students who experience underachievers are those who have learning outcomes that are not in accordance with their intelligence. This study aims to determine the factors that influence students to experience underachievers. Research with this literature study results that underachiver is influenced by several factors such as: the playing environment related to communication and interaction with peers and their associates, the learning environment, namely school conditions and learning styles provided by the teacher, and the family environment, namely parenting patterns, interaction and communication among family members, as well as the trust given to children.